2001
DOI: 10.1007/bf01280311
|View full text |Cite
|
Sign up to set email alerts
|

On the alignment of cellulose microfibrils by cortical microtubules: A review and a model

Abstract: The hypothesis that microtubules align microfibrils, termed the alignment hypothesis, states that there is a causal link between the orientation of cortical microtubules and the orientation of nascent microfibrils. I have assessed the generality of this hypothesis by reviewing what is known about the relation between microtubules and microfibrils in a wide group of examples: in algae of the family Characeae, Closterium acerosum, Oocystis solitaria, and certain genera of green coenocytes and in land plant tip-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
311
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 390 publications
(329 citation statements)
references
References 198 publications
11
311
0
2
Order By: Relevance
“…In general, the orientation of cellulose microfibrils in the cell wall governs many plant functions (Burgert and Fratzl 2009). Again, there is much evidence that the major factor in controlling microfibril orientation during cell growth is the orientation of the cortical microtubules, but some other factor must also be involved (Baskin 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In general, the orientation of cellulose microfibrils in the cell wall governs many plant functions (Burgert and Fratzl 2009). Again, there is much evidence that the major factor in controlling microfibril orientation during cell growth is the orientation of the cortical microtubules, but some other factor must also be involved (Baskin 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic analysis and inhibitor studies indicate that cytoplasmic microtubules play an important role in guiding the orientation of the deposition of cellulose microfibrils (reviewed in Baskin, 2001), and the cellulose synthase rosette was found to move along the plasma membrane in tracks that largely coincided with the cortical microtubules (Paredez et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The shape of whole plant body is predominantly regulated by anisotropic growth of individual cells. Cortical microtubules, a characteristic cytoskeleton in interphase cells of plants, are likely involved in the modification of growth anisotropy of cells through the regulation of the orientation of cellulose microfibrils (Shibaoka, 1994;Baskin, 2001;Paredez et al, 2006). We have shown that the gravitational force affected the orientation of cortical microtubules during modification of anisotropic growth of stems.…”
Section: Introductionmentioning
confidence: 89%